Overcoming Low Adherence to Chronic Medications by Improving their Effectiveness using a Personalized Second-generation Digital System - Bayatra, Areej; Nasserat, Rima; Ilan, Yaron (Current Pharmaceutical Biotechnology, 2024)
Introduction: Low adherence to chronic treatment regimens is a significant barrier to improving clinical outcomes in patients with chronic diseases. Low adherence is a result of multiple factors. Methods: We review the relevant studies on the prevalence of low adherence and present some potential solutions. Results: This review presents studies on the current measures taken to overcome low adherence, indicating a need for better methods to deal with this problem. The use of first-generation digital systems to improve adherence is mainly based on reminding patients to take their medications, which is one of the reasons they fail to provide a solution for many patients. The establishment of a second-generation artificial intelligence system, which aims to improve the effectiveness of chronic drugs, is described. Conclusion: Improving clinically meaningful outcome measures and disease parameters may increase adherence and improve patients' response to therapy.
Keywords: Artificial intelligence